واقع ممارسة المشرف المقيم في مدارس التعليم العام بمدينة عمران لمعايير الإشراف التربوي بالجمهورية اليمنية - مغربه فهد صالح; السودي مبروك صالح; المرهبي يحي أحمد; الشطبي رقية يحي (Journal of Amran University, 2023)
This study aimed to investigate the reality of the practice of resident educational supervisors in public education schools in Amran, Yemen, according to the standards of educational supervision of the Yemeni Ministry of Education, from the perspective of teachers. The study used a descriptive analytical method and a questionnaire to survey a random sample of 107 teachers. The results showed that the level of performance of resident educational supervisors in Amran schools was rated very good. The highest average was in the school organization domain, followed by supervisory implementation, follow-up and development of performance, and learning planning and learning. The study also found that there were statistically significant differences in the assessment of the level of performance of resident educational supervisors depending on gender, academic qualification, and years of experience. Females, those with university qualifications, and those with less than five years of experience rated the supervisors more highly. The study recommended the development of the capacities of resident educational supervisors and training them on all professional skills related to their field of work.